Pathology of the Proximal Radius in Juvenile Pugs - Obel, Christina; Rondahl, Veronica; Rohdin, Cecilia; Friling, Lisa; Bergström, Annika (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
The aim of this study was to describe the physeal pathology of the proximal radius in four skeletally immature male Pugs. Physical examination, radiography, and computed tomography (CT) of the thoracic limbs were performed in all four dogs. Two Pugs were available for long-term follow-up and two Pugs were euthanatized after the diagnostic imaging results. Four male Pugs, aged between 6 and 7 months, were presented with a history of thoracic limb lameness lasting 2 to 3 months. Radiography and CT of the thoracic limbs showed irregularity of the proximal radial physes with varying degrees of radiolucency within the adjacent metaphyses. The pathology was associated with elbow joint incongruity and angular deformity of the antebrachium. Two dogs were euthanatized, one of which was autopsied, and histopathology of the proximal radius revealed bilateral physeal dysplasia. At long-term follow-up of the two surviving dogs, lameness had resolved. Radiography and CT scans of the thoracic limbs revealed normal bone opacity within the proximal radius and resolution of the radiolucent areas of the proximal radial physes. However, incongruity of the radioulnar joint remained. In this report, the resolution of identified physeal pathology at the proximal radius in juvenile Pugs demonstrates the potential for spontaneous remission despite the presence of notable radiographic changes.
Keywords: physeal dysplasia; radius; Pugs; physeal fracture